Antioxidant Capacity of the Leaf Extract Obtained from Arrabidaea chica Cultivated in Southern Brazil - Siraichi, Jackeline Tiemy Guinoza (Public Library of Science, 2013)
Arrabidaea chica leaf extract has been used by people as an anti-inflammatory and astringent agent as well as a remedy for intestinal colic, diarrhea, leucorrhea, anemia, and leukemia. A. chica is known to be a good producer of phenolics. Therefore, in the present study, we investigated its antioxidant activity. The phenolic composition of A. chica leaves was studied by liquid chromatography coupled to diode array detection (LC–DAD) and liquid chromatography coupled to electrospray ionization-tandem mass spectrometry (LC–ESI-MS/MS), and isoscutellarein, 6-hydroxyluteolin, hispidulin, scutellarein, luteolin, and apigenin were identified. The extract from leaves of A. chica was tested for antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, β-carotene bleaching test, and total reactive antioxidant potential (TRAP) method. The crude extract quenched DPPH free radicals in a dose-dependent manner, and the IC(50) of the extract was 13.51 µg/mL. The β-carotene bleaching test showed that the addition of the A. chica extract in different concentrations (200 and 500 µg/mL) prevented the bleaching of β-carotene at different degrees (51.2% ±3.38% and 94% ±4.61%, respectively). The TRAP test showed dose-dependent correlation between the increasing concentrations of A. chica extract (0.1, 0.5, and 1.0 µg/mL) and the TRAP values obtained by trolox (hydro-soluble vitamin E) 0.4738±0.0466, 1.981±0.1603, and 6.877±1.445 µM, respectively. The 2 main flavonoids, scutellarein and apigenin, were separated, and their antioxidant activity was found to be the same as that of the plant extract. These 2 flavonoids were quantified in the plant extract by using a validated HPLC-UV method. The results of these tests showed that the extract of A. chica had a significant antioxidant activity, which could be attributed to the presence of the mixture of flavonoids in the plant extract, with the main contribution of scutellarein and apigenin.